Metasynthesis of Preservice Professional Preparation and Teacher Education Research Studies - Carl J. Dunst; Deborah W. Hamby; Robin B. Howse; Helen Wilkie; Kimberly Annas (MDPI AG, 2019)
Results from a metasynthesis of the relationships between 14 different types of preservice teacher preparation practices and teaching quality, preschool to university student performance, and university student and beginning teacher belief appraisals are reported. Each type of preservice practice (e.g., course-based student learning) included different kinds of instructional methods (e.g., problem-based learning, inquiry-based learning, and project-based learning). The metasynthesis included 118 meta-analyses and 12 surveys of more than three million study participants. Findings clearly indicated that active university student and beginning teacher involvement in mastering the use of instructional practices and both knowledge and skill acquisition by far stood out as the most important preservice teacher preparation practices. These included extended student teaching experiences, simulated instructional practices and microteaching, faculty coaching and mentoring, clinical supervision, different types of cooperative learning practices, and course-based active student learning methods. The pattern of results helped identify high leverage and high impact teacher preparation practices. Implications for future research and improving teacher preparation are described.